Unmasking the hidden culprit: neurosyphilis mimicking parkinsonism in a middle-aged male - Zhaobo Shi; Yong Sun; Xinsheng Han (BMC Neurology)
Abstract Background General paresis, a tertiary manifestation of neurosyphilis affecting the brain, is characterized by mental and behavioral disorders, such as attention disorder, cognitive impairment, and personality changes. But parkinsonism is rarely reported in patients with neurosyphilis, let alone general paresis. This study reports a case suffering from both general paresis and parkinsonism. Case presentation A 50-year-old man was initially misdiagnosed with “alcohol-related psychiatric and behavioral disorders” due to the onset of psychiatric symptoms following alcohol abstinence. The excessive administration of psychotropic medications, attributed to their limited efficacy, was identified as the primary cause of his subsequent extrapyramidal symptoms, including tremor and bradykinesia. However, treatment with levodopa yielded only marginal effectiveness. Following a comprehensive diagnostic evaluation, which encompassed brain magnetic resonance imaging, syphilis screening, and cerebrospinal fluid analysis, neurosyphilis was ultimately identified as the underlying etiology. Subsequent treatment with aqueous penicillin resulted in a marked improvement in his symptoms. Conclusion This case illustrates a rare manifestation of neurosyphilis, specifically parkinsonism. The diagnostic process was complicated by several confounding factors. As neurosyphilis is known as the “great imitator,” capable of mimicking various neuropsychiatric disorders, routine syphilis screening is imperative for patients presenting with mental disorders and parkinsonian symptoms to facilitate early diagnosis and enhance prognosis.